2021
DOI: 10.1186/s12941-021-00477-0
|View full text |Cite
|
Sign up to set email alerts
|

Wide spread and diversity of mutation in the gyrA gene of quinolone-resistant Corynebacterium striatum strains isolated from three tertiary hospitals in China

Abstract: Background Corynebacterium striatum was confirmed to be an important opportunistic pathogen, which could lead to multiple-site infections and presented high prevalence of multidrug resistance, particularly to quinolone antibiotics. This study aimed to investigate the mechanism underlying resistance to quinolones and the epidemiological features of 410 quinolone-resistant C. striatum clinical strains isolated from three tertiary hospitals in China. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(34 reference statements)
2
2
0
Order By: Relevance
“…Corynebacterium striatum was generally resistant to ciprofloxacin (95.6%) in our study, which is consistent with the result reported by Wang Y. et al (2021) that 100.0% (410/410) of Corynebacterium striatum were resistant to ciprofloxacin. In our study, the resistance rate of Micrococcus luteus to erythromycin was 36.3%, and the resistance rate to clindamycin was 17.5%, which may indicate that a high number of infections caused by Micrococcus luteus resistant to ERY and CLI may fail therapy.…”
Section: Discussionsupporting
confidence: 93%
“…Corynebacterium striatum was generally resistant to ciprofloxacin (95.6%) in our study, which is consistent with the result reported by Wang Y. et al (2021) that 100.0% (410/410) of Corynebacterium striatum were resistant to ciprofloxacin. In our study, the resistance rate of Micrococcus luteus to erythromycin was 36.3%, and the resistance rate to clindamycin was 17.5%, which may indicate that a high number of infections caused by Micrococcus luteus resistant to ERY and CLI may fail therapy.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, almost all of the C. striatum strains investigated in this study were multidrug -resistant. They were only sensitive to vancomycin, linezolid and daptomycin, consistent with some previous global studies [ 5 , 16 , 17 ]. C. striatum isolates were mainly isolated from lower respiratory tract specimens (51.85%, 14/27).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the QRDR at gyrA gene was amplified and sequenced as previously described. 8 , 28 , 31 , 32 In this study, the sequenced data of the gyrA gene from 42 ciprofloxacin-resistant isolates were compared to those from susceptible ones. Table 5 summarizes the associations between ciprofloxacin MICs and mutations in the gyrA QRDRs of ciprofloxacin-resistant isolates.…”
Section: Resultsmentioning
confidence: 99%